Vision of a Service Value Network in Maritime Container Logistics - Jürgen W. Böse; Carlos Jahn; Raman Sarin (Next Generation Supply Chains: Trends and Opportunities. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 18, 2014)
Against the backdrop of stagnant or slow volume growth in the international container transport, liner shipping companies make considerable efforts to reduce costs and provide better service quality. Due to the strategic character of decisions associated with the implementation and reorganization of liner services, solution approaches that enable a substantial reduction of total roundtrip time without appreciable extra costs are regarded as promising. For this purpose, the authors develop the idea of a Maritime Service Value Network representing cooperation among container terminals as well as at least one ship routing company and one meteorological service provider. The network aims at acceleration of container liner services with (ideally) cost-neutral operations measures. The proposed concept can provide the container terminals with considerable competitive advantages and simultaneously put the liner shipping companies in a strong position for successful integration in global supply chain networks. The full paper gives an estimate of the magnitude of existing time saving potential and the associated economic and operational impact. Additionally, a rough description of the network idea is presented and obstacles for network coordination are highlighted.
10419/209187; https://econpapers.repec.org/RePEc:zbw:hiclpr:18
Keywords: 650; container liner service; service value network; time savings; weather routing